Perspective relationnelle du développement féminin - Spain, Armelle; Hamel, Sylvie (Canadian Journal of Counselling and Psychotherapy, 1996)
While considering self-development as a gradual separation from significant others, the current theoretical conceptualizations of adult psychological development call into question an evolution that would be realized through relationships. Nonetheless, recent research on women's identity shows that their sense of self is formed within the context of their interactions with others. Thus, the relational component of women's development is put into focus. Three sources of this field of psychology are briefly presented and discussed in this article: the works of Josselson, Gilligan and the Wellesley College's Stone Center. The relational perspective on development suggests reconsidering theories and practices in psychology and consequently in career counselling.